Phase separation of Nur77 mediates XS561-induced apoptosis by promoting the formation of Nur77/Bcl-2 condensates - Xiaohui Chen; Meichun Gao; Yongzhen Xia; Xin Wang; Jingbo Qin; Hongying He; Weirong Liu; Xiaowei Zhang; Shuangzhou Peng; Zhiping Zeng; Ying Su; Xiaokun Zhang (Elsevier, 2024)
The orphan nuclear receptor Nur77 is a critical regulator of the survival and death of tumor cells. The pro-death effect of Nur77 can be regulated by its interaction with Bcl-2, resulting in conversion of Bcl-2 from a survival to killer. As Bcl-2 is overexpressed in various cancers preventing them from apoptosis and promoting their resistance to chemotherapy, targeting the apoptotic pathway of Nur77/Bcl-2 may lead to new cancer therapeutics. Here, we report our identification of XS561 as a novel Nur77 ligand that induces apoptosis of tumor cells by activating the Nur77/Bcl-2 pathway. In vitro and animal studies revealed an apoptotic effect of XS561 in a range of tumor cell lines including MDA-MB-231 triple-negative breast cancer (TNBC) and MCF-7/LCC2 tamoxifen-resistant breast cancer (TAMR) in a Nur77-dependent manner. Mechanistic studies showed XS561 potently induced the translocation of Nur77 from the nucleus to mitochondria, resulting in mitochondria-related apoptosis. Interestingly, XS561-induced accumulation of Nur77 at mitochondria was associated with XS561 induction of Nur77 phase separation and the formation of Nur77/Bcl-2 condensates. Together, our studies identify XS561 as a new activator of the Nur77/Bcl-2 apoptotic pathway and reveal a role of phase separation in mediating the apoptotic effect of Nur77 at mitochondria.